Antifertility activities of srikaya leaves (Annona squamosa L.) ethanol extract against reproduction system : spermatogenesis and quality sperm study - Nur Laili Dwi Hidayati; Tita Nopianti; Nur Rahayuningsih; Yuliana Dewi; Yani Suryani (Universitas Ahmad Dahlan, 2018)
The use of male contraceptives is still limited to condoms and vasectomy. However, their applications have frequently led to complaints, making male participation in family planning programs persistently low. Therefore, developing contraceptive drugs from parts of plants with antifertility activity becomes necessary. This study aimed to identify the antifertility activity of sugar apple leaves ethanol extract in spermatogenesis and sperm quality in test animals. There were four treatment groups: control (suspension PGA 1%), Dose I (24.2 g/Kg BW rat), Dose II (48.4 mg/Kg BW rat), and Dose III (96.8 mg/Kg BW rat). The test preparation was administered orally for 48 days. The effect on spermatogenesis was observed from the testicular index (%), seminiferous tubule diameter (μm), and the number of spermatogenic cells and spermatocytes. The sperm quality was determined from sperm motility, concentration, and morphology. All of these parameters were statistically analyzed using ANOVA. The results showed that the testicular index and the number of spermatogenic cells and spermatocytes in all groups of rats were significantly reduced. The administration of the ethanolic extract of sugar apple leaves also decreased the seminiferous tubule diameter with a significant size shrinkage in Dose III. Sperm quality analysis revealed a reduction in sperm count and motility and a significant increase in sperm abnormalities in all doses. The antifertility activity (i.e., the reduction of sperm count and motility) in rats receiving Dose III was similar to the ones in Dose II. Therefore, the best dose of antifertility activity is Dose III (96.8 mg/Kg BW rat), implying that it has the potential as male contraceptive.